Negation marker in Standard Persian : a typological analysis based on Givon’s functional model: عامل نفی در زبان فارسی معیار: بررسی رده‌شناختی براساس مدل نقش‌ گرایی گیون (Journal of the College of Languages (JCL), 2024)
Typological analysis about  the negation marker  in different languages is one of the fields of research that has attracted much attention.  In Persian language, this constituent has been analysed from different aspects. This study aimed to analyse  different aspects of negation marker  in  the adjectives,  the noun phrases and  the verb phrases based on typological analysis.  Many studies have been revealed that  the negation in adjectives has shown lexically and morphologically. In the noun phrases, /hich/  has used as a negative marker necessarily marking the verb phrase as negative too. In the verb phrases, negation occurs morphologically by the addition of the prefix /na/(no) or its variations. In  the modal auxiliaries /khastan/ and /tawanestan/(can), aspectual auxiliary /budan/ (be) and lexicalized auxiliary /bayad/(must) negative marker occurs either before the auxiliary or before the main verb. Moreover, in the modal auxiliary /shodan/(will be)  and the lexicalized word /shayad/ (perhaps)  only the main verb is negated. However, aspectual auxiliary /dashtan/ (to have) has shown a different behavior in that its negative form and the negative form of the modal auxiliary become neutral. Negation filed in the  verb phrases and morphological negative adjectives is narrow and only a portion of negative proposition falls under the field of negation while negative field in the noun phrases is broad and includes the entire proposition.چکیده:بررسی رده‌شناختی سازه نفی در زبان‌های گوناگون بسیار مورد توجه قرار گرفته است. در زبان فارسی این سازه از بسیاری جهات قابل بررسی می‌باشد. این پژوهش کوشیده است با نگاهی رده‌شناختی به سازه نفی، جنبه‌های مختلف عامل نفی در صفات، گروه‌های اسمی و گروه‌های فعلی را بررسی کند. بررسی‌ها نشان می‌دهند نفی در صفات به صورت ساخت‌واژی و واژگانی اتفاق می‌افتد. نفی در گروه‌های اسمی به کمک عامل منفی "هیچ" صورت می‌پذیرد که با منفی‌شدن اسم یا گروه اسمی، فعل نیز الزاما منفی می‌شود. در گروه‌های فعلی نفی به صورت ساختواژی با افزودن پیشوند "نـ" اتفاق می‌افتد. در فعل‌های معین وجه‌نمای "خواستن و توانستن"، فعل معین نمودنمای "بودن" و فعل معین واژگانی‌شده "باید" سازه منفی هم پیش از فعل معین قرار می‌گیرد هم پیش از فعل واژگانی. در فعل معین  وجه‌نمای "شدن" و فعل واژگانی‌شده "شاید"، تنها فعل واژگانی منفی می‌شود. فعل معین  نمودنمای "داشتن" رفتار متفاوتی از خود به نمایش می‌گذارد و تقابل صورت منفی این فعل نمودنما با صورت منفی وجه‌نمای آن خنثی می‌شود. سیطره عامل نفی در گروه‌های فعلی و صفات منفی ساخت‌واژی محدود بوده و تنها بخشی از گزاره را در بر می‌گیرد. در صورتی‌که سیطره نفی در گروه‌های اسمی گسترده و  دربرگیرنده همه گزاره است.Received on 23/6/2023  Accepted on 20/8/2023  Published on 2/1/2024